Meningitis Caused by in an Apparently Immunocompetent Patient - Shervin Shokouhi MD; Atousa Hakamifard MD (SAGE Publishing, 2022)
Cryptococcal meningitis (CM), as a life-threatening opportunistic infection, often is among cases with cell-mediated immunodeficiencies, such as AIDS, hematologic malignancies, and solid organ transplant recipients. Cryptococcal meningitis in healthy individuals is uncommon, and its detection in immunocompetent cases may be tricky because the presentation is generally more indolent than the traditional meningitis presentation, leading to late diagnosis and potential sequels. We present a CM case in an immunocompetent Iranian male patient who was treated successfully.